The Projected Precipitation Reduction over the Central Andes may Severely Affect Peruvian Glaciers and Hydropower Production. (November 2016) - Kronenberg, Marlene; Schauwecker, Simone; Huggel, Christian; Salzmann, Nadine; Drenkhan, Fabian; Frey, Holger; Giraáldez, Claudia; Gurgiser, Wolfgang; Kaser, Georg; Juen, Irmgard; Suarez, Wilson; Hernaández, Javier Garćía; et al.
Abstract: Water from glaciers is crucial for the Peruvian hydropower production. Hence, we investigate the glacier-atmosphere and climate interactions in the Cordillera Vilcanota, considering scenarios of significant precipitation reductions until 2100. The glacier mass balance model ITGG-2.0 is used for analysing the energy balance components regarding the projections. The results indicate that a precipitation decrease not only affects the accumulation rate of glaciers but also influences the ablation energy availability. Therefore, glacier retreat in the Central Andes is expected to accelerate, making water availability unsustainable and likely leading to future shortages for the hydropower sector and for other water consuming systems.